2020
DOI: 10.3390/healthcare8030272
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Incident Triage in Radiation Oncology Incident Learning System

Abstract: The Radiotherapy Incident Reporting and Analysis System (RIRAS) receives incident reports from Radiation Oncology facilities across the US Veterans Health Affairs (VHA) enterprise and Virginia Commonwealth University (VCU). In this work, we propose a computational pipeline for analysis of radiation oncology incident reports. Our pipeline uses machine learning (ML) and natural language processing (NLP) based methods to predict the severity of the incidents reported in the RIRAS platform using the textual descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In this study, we showed that the performance of the ULMFiT-based algorithm varied from good to excellent in classifying patients’ smoking status from Finnish narrative reports. Overall, ULMFiT and other deep learning-based approaches have shown to be promising tools in standardization of language used in narrative reports including abbreviations, acronyms, eponyms, slang and jargon words [ 18 , 19 ]. An additional benefit of using this type of language model is that, once fine-tuned for Finnish medical narratives, the classifier can be further developed for other study needs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed that the performance of the ULMFiT-based algorithm varied from good to excellent in classifying patients’ smoking status from Finnish narrative reports. Overall, ULMFiT and other deep learning-based approaches have shown to be promising tools in standardization of language used in narrative reports including abbreviations, acronyms, eponyms, slang and jargon words [ 18 , 19 ]. An additional benefit of using this type of language model is that, once fine-tuned for Finnish medical narratives, the classifier can be further developed for other study needs.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the only published report of using NLP-ML methods to automate incident learning was by Syed et al in 2020. 38 In their study, they used traditional ML as well as transfer learning methods to perform binary classification of incident severity (high vs. low). Therefore, our work complements the literature by providing first-hand insight into the capability of NLP-ML methods to classify three other radiotherapy inci- 38 reported that the Linear Support Vector Machine (SVM) was the optimal ML model for their radiation oncology incident report data.…”
Section: Discussionmentioning
confidence: 99%
“…38 In their study, they used traditional ML as well as transfer learning methods to perform binary classification of incident severity (high vs. low). Therefore, our work complements the literature by providing first-hand insight into the capability of NLP-ML methods to classify three other radiotherapy inci- 38 reported that the Linear Support Vector Machine (SVM) was the optimal ML model for their radiation oncology incident report data. This is consistent with our result, as our optimal ML model was the Linear SVR model, which is a regressor derivative of SVM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations